Corrosion of x-70 carbon steel pipeline subject to sulfate reducing bacteria - Mohd. Ali, Muhammad Khairool Fahmy (Asian Research Publishing Network, 2016)
Carbon steels are commonly used as structural materials of piping systems in oil and gas industry because of their lower cost and wider availability despite their relatively lower corrosion resistance. This work investigates the preferable growth media for Sulfate Reducing Bacteria to proliferate rapidly and the effect of Microbiologically Influenced Corrosion activity towards carbon steel API 5L X-70 line pipe. Present research work highlighted that the preferred growth medium for ATCC 7757 and BARAM is Modified Baar's and Postgate C for Sg. Ular types of SRB. In addition, the corrosion rate was calculated using data based on metal weight loss experiment. The result confirmed that the corrosion rate in biotic (presence of Sulfate Reducing Bacteria) environment is much higher compared to abiotic environment (absence of Sulfate Reducing Bacteria). The pitting morphology that developed with time due to SRB activity was characterized with Field Emission Scanning Electron Microscopy and Energy dispersive spectroscopy. It shows high peak of Sulfur (S) and Iron (Fe) present after exposure to biotic compared to the abiotic sample. Field Emission Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy results show that corrosion activity due to Sulfate Reducing Bacteria will form biofilm and iron sulfide layer on the metal surface. Future research should emphasize using local strain bacteria rather than microorganisms from culture collection sample to represent the activity and the effect or impact of microorganisms from the actual site